Design Thinking Approach for Culture Sensitive Tourism: (Case Study of Cultural Degradation of Baduy Tribe Due to Tourism) - Pradana, Triandi; Sofiani; Tanu, Barbie Valerina (Yayasan Ilomata, 2025)
Tourism that is developing in the Baduy region has now caused cultural degradation due to tourism activities, especially those involving tour guides from the Baduy tribe. The urgency of this study is the need for a study of tourism models that can adapt to the provisions of customary rules. The purpose of this study is to make recommendations for a culturally friendly tourism concept model that is suitable for application in Baduy so as not to degrade the culture of the Baduy tribe. This study uses a qualitative method with a design thinking approach. Data were collected through interview techniques, observation, and documentation studies. The selection of informants was carried out using purposive sampling techniques. Data obtained will then be analyzed using the interactive model technique from Miles & Huberman. This study recommends the ethno-ecotourism model as a culturally appropriate and sustainable tourism approach for the Baduy region. Through the design thinking process, a prototype model was developed and translated into a policy recommendation tailored to the Baduy context. Future testing is needed to evaluate the model’s alignment with community needs, and its implementation requires collaboration within a quadruple helix framework involving government, academia, communities, and media. However, despite its potential, the ethno-ecotourism model faces critical limitations, particularly in ensuring genuine community participation in decision-making. Studies show that top-down governance often marginalizes local voices, leading to a gap between projected and realized benefits.